A new friend - Neal, Michael; Dominguez, Luis, 1923- (New York : Golden Book, 1984)
Billy's father brings him a wonderful gift: his own gremlin named Gizmo.
K-3
K-3
Keywords: Pets -- Fiction; Fantasy fiction